TRANSFORMASI PADANAN KATA BAHASA INDONESIA DALAM TREND KONTEN TIKTOK: TRANSFORMASI PADANAN KATA BAHASA INDONESIA DALAM TREND KONTEN TIKTOK (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the transformation of Indonesian equivalents appearing in trending content on the social media app TikTok. Advances in digital technology and the increasing use of social media have given rise to new forms of language use, including the issue of equivalents (Hidayat, 2020). This research aims to identify and explain how Indonesian equivalents have transformed within the creative content space on TikTok. This study includes problem identification to clarify the details of the problem. Based on this formulation, the problem identification in this research is as follows: The large number of foreign or new terminologies used in TikTok content that do not have official equivalents in Indonesian (Fajri, 2021). The use of equivalent terms in TikTok content often does not conform to Indonesian language rules (Purwono, 2024). There is a lack of awareness among social media users, especially TikTok users, of the importance of using good and correct Indonesian (Susanti, 2022). The method used is descriptive qualitative, with data collection techniques through observation and documentation of trending TikTok content during a specific period (Darmalaksana, 2020). The analysis was conducted by tracing the use of words that experienced changes in meaning, expansion of meaning, or the creation of new equivalents that deviate from standard rules. The research results show that trends on TikTok encourage the formation of a variety of equivalent terms influenced by user creativity, popular language styles, and the need for expressions relevant to digital culture (Setiawan, 2020). These findings indicate that social media plays a dynamic role in the formation and transformation of the Indonesian language in the modern era. Keywords: Transformation of equivalent terms on TikTok, Indonesian